Passively Mode-Locked Ytterbium-Doped Fiber Laser Based on SnS2 as Saturable Absorber - Jian Li; Yuefeng Zhao; Qingyun Chen; Kangdi Niu; Ruyi Sun; Huanian Zhang (IEEE Photonics Journal)
In this letter, tin disulfide (SnS2) nanosheets were employed as saturable absorber for obtaining passively mode-locked Yb-doped fiber laser. A SnS2-PVA film was fabricated by incorporating the SnS2 nanosheets with the polyvinyl alcohol (PVA), Based on the SnS2-PVA film as saturable absorber, passively mode-locked Yb-doped fiber laser at a central wavelength of 1062.66 nm was achieved. The 3-dB bandwidth, pulse width, pulse repetition rate, and maximum average output power were 8.63 nm, 656 ps, 39.33 MHz, and 2.23 mW, respectively. The results exhibit that SnS2 has excellent saturable absorption properties, which are equivalent to the reported two-dimensional transition metal dichalcogenides (WS2, MoS2) and will have wide potential applications in the field of ultrafast photonics.